Comprehensive review of bandwidth usage analysis with Simple Network Management Protocol (SNMP) in FSKM Laboratory - Muhammad Bakhit, Balqis Aini; Mohd Yusof, Mohd Azahari; Buja, Alya Geogiana (College of Computing, Informatics, and Mathematics, 2025)
This project focuses on improving network management and monitoring in all educational institutions by focusing on FSKM laboratory. Network monitoring is very important in educational institutions as it ensures connectivity runs well, helps in a successful use of bandwidth for better performance and online learning tools. Therefore, this paper aims to discuss the lack of comprehensive data concerning network performance. The main objectives are monitoring bandwidth usage using SNMP, visualizing performance metrics through PRTG, Zabbix, and Nagios, and analyzing traffic patterns to identify network inefficiencies. The methodology involved the use of Wi-Fi networks (UiTM WiFi STUDENT), implementing of SNMP agents on the devices, configuration of network monitoring tools, and collecting real-time data over three weeks. The collected results showed that Nagios gave consistent and reliable monitoring with no packet loss, Zabbix illustrated low latency with efficient resource usage, while PRTG offered userfriendly interfaces but showed limitations under high traffic. These findings define the strengths and weaknesses of each tool, highlighting the need to select suitable tools based on network requirements. In addition, this research shows how SNMP-based monitoring allows for better bandwidth, improvement of performance, and stable connectivity within educational environments.